Kontanthjælpsmodtagerens kritiske register: Den civile, den industrielle og den domestiske protest - Nielsen, Mathias Herup (Slagmark - Tidsskrift for idéhistorie, 2015)
This article investigates different acts of political protests currently floating from unemployed citizens who are being affected by recent retrenchment policy reforms. Whereas most of the existing literature tends to portray political protest as either collective and public or individual and private, this article attempts instead to shed light on the plurality of normative resources activated by the unemployed in a highly critical situation. Thereby the analysis moves between the collective and the individual as well as between the public and the private. Using the theoretical framework developed by Laurent Thévenot and Luc Boltanski in their joint work on justification, the article analyses a specific case, namely unemployed Danish recipients of social assistance who are affected by a new policy initiative meaning that their income has been lowered. Drawing on newspaper articles and qualitative in-depth interviews with affected citizens, the analysis unfolds and theorizes upon three very different forms of protesting: a civic, an industrial and a domestic form of resistance.